The Influence Of Personal Branding And Social Media Engagement On Enhypen Fan Loyalty In Surabaya - Wulandari, Nurul Nur Rohmawati; Nurhadi (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The rise of the Korean Wave (Hallyu), especially K-pop, has fostered loyal fan bases globally, including in Indonesia. Enhypen, a prominent K-pop group, has experienced significant growth in fan engagement and loyalty. This research investigates the simultaneous and partial effects of personal branding and social media engagement on fan loyalty among Enhypen fans in Surabaya. Data were collected through purposive sampling with 164 respondents who met specific demographic and behavioral criteria. The study used a structured questionnaire and analyzed the data using statistical tools such as validity and reliability testing, multiple linear regression, and hypothesis testing. The results show that both personal branding and social media engagement have a significant positive influence on fan loyalty, with social media engagement being the more dominant factor. These findings underscore the importance of digital interaction and authentic self-representation in fostering long-term fan relationships. The research offers valuable implications for marketing strategies within the entertainment industry, especially in managing artist branding and digital community engagement.